Caracterização espectro temporal de lavouras de arroz irrigado por meio de imagens modis - Nobre, Felipe Luiz de Lemos (2010)
The objective of this study was to look into the viability of using the images acquired by the Moderated Orbital resolution Imaging Spectroradiometer (MODIS) sensor in order to determining the period of occurrence of phenological stages in order to assist determining the best conducive to harvesting of seed rice. The study area consisted of 12 farms located in the municipalities of Arroio Grande and Rio Grande - RS, of which we had information regarding to sowing, V4, R1, R6 and harvest dates. The delimitation of the field crops was performed by geodetic coordinates obtained by a GPS navigation receiver, aided by medium spatial resolution images from Landsat-5 Thematic Mapper (TM) sensor. In order to generate the spectro-temporal profiles were used daily images from MODIS sensor products MOD09GQ (Terra satellite) and MYD09GQ (Aqua satellite) with 250m spatial resolution, turned in the Enhanced Vegetation Index 2 (EVI2), ranging from before sowing to after harvest. Daily images from Terra and Aqua satellites were composited in images containing the maximum EVI2 for each day. Then we excluded from the analysis the composite images with cloud cover noise contamination and those showing values significantly discrepant with those of adjacent days. The temporal profiles of EVI2 for each crop field were associated with the dates of sowing, V4, R1 and R6 phenological stages and harvesting of crops fields. The EVI2 spectro-temporal profile for paddy rice presented considerable increases around the V4 stage, reaching its highest values around the R6 stage and then begin to decrease even after harvesting. However, we observed a wide range of EVI2 values for each developmental stage analized and the harvest date for different crops fields. Thus, in this study we could not establish reliable parameters that indicate the possibility of using daily images from MODIS as a single indicator for determining both phenological stages and most propitious time for rice harvesting. However, it is possible to monitor the temporal profile EVI2 of irrigated rice fields, which can be used as auxiliary data to approximately determine the crop phonological stage, since cloud free images are available.